Rapid Resolution of Polyhydramnios Foretells Circulatory Collapse for the Donor Twin in Feto-Fetal Transfusion Syndrome - López-Cepero, Ronald; Santoro, Joseph; de la Vega, Alberto (Puerto Rico Health Sciences Journal, 2016)
Feto-fetal transfusion syndrome is a pathological process unique to diamniotic monochorionic pregnancies. It is the consequence of an unbalanced fetal blood flow through communicating vessels within a shared placenta. When it occurs, a polyuric, hypervolemic recipient twin co-exists with a hypovolemic oliguric donor. The presence of polyhydramnios or oligohydramnios is considered a poor prognostic indicator, whereas normal amniotic fluid volumes indicate a lack of clinically significant twintwin transfusion. In addition, the spontaneous normalization of amniotic fluid volume is usually seen as a favorable prognostic sign. Here, however, we present a case of feto-fetal transfusion in a 31 year-old primigravida at 19 week, in which the spontaneous normalization of amniotic fluid volume in the recipient twin preceded the death of the donor.